Development of Maze Case Games Based on Word Walls the Theme of My Heroes in Improving Elementary School Students' Critical Thinking Ability - Yuli Mulyawati; Yuyun Elizabeth (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2023)
The role of schools and teaching staff play an important role in the era of society 5.0. especially during a pandemic, learning activities take place through online media using various supporting applications, such as zoom, google classroom, google class Meetings, and others. The use of this application media requires more insight from educators. However, in reality, currently, not all educators have sufficient information technology so learning carried out online looks monotonous and difficult for students to understand. Learning focuses more on face-to-face with zoom, the teaching materials displayed are only in the form of words or power points, the teacher's explanations are more verbal, not using applications or interactive learning media so that the reasoning and creative power of students is not well explored. The problem was recognized and based on the narrative of several teachers at SDN Panaragan 1, Bogor City when the researchers made initial observations at the school regarding the problems that existed in elementary schools. Efforts that can be made to overcome monotonous learning are interactive educational games, namely word wall-based maze games. The aim is to see an overview of the Improvement and Effectiveness of the Wordwall-Based Maze Chase Game Development in improving the critical thinking and reasoning abilities of Elementary School students/ The method used is Research and Development, namely development in learning media. The learning media development model used is analysis, design, development, implementation, and evaluation. Based on research data , maze chase is an appropriate educational game to be used as a learning medium. Based on data processing results, 93.3% of students stated that the educational games given by the teacher challenged them to fill it properly. Moreover, games are made in the form of labyrinths that challenge students to think critically and reason. Whereas 6.7% of students or a small portion stated that educational games were not challenging for them to fill properly.